Lipocalin 2 Upregulation Protects Hepatocytes from IL1-β-Induced Stress - Ying Hu; Jihua Xue; Ying Yang; Xiaotang Zhou; Chaochao Qin; Min Zheng; Haihong Zhu; Yanning Liu; Weixia Liu; Guohua Lou; Jing Wang; Shanshan Wu; et al. (Cellular Physiology and Biochemistry, 2015)
Background: Lipocalin 2 (LCN2), a protein primarily produced by hepatocytes, is highly upregulated under various conditions that induce cellular stress, such as intoxication, infection or inflammation. However, the precise biological functions and underlying mechanisms of LCN2 in hepatocytes remains unknown. Methods: Hepatocyte stress was successfully induced by treating Huh7 cells with interleukin-1β (IL-1β). Interleukin-6 (IL-6), Tumor Necrosis Factor-α (TNF-α) and LCN2 levels were measured in IL-1β treated Huh7 cells and supernatant. Additionally, microarray analysis was conducted to identify genes differentially expressed in LCN2-silenced and control Huh7 cells. Results: TNF-α, IL-6 and LCN2 were significantly elevated in Huh7 cells after IL-1β) treatment. In LCN2-silenced Huh7 cells, expression of IL-6 and TNF-α was significantly increased when compared with the expression levels of control Huh7 cells. Furthermore, differentially expressed genes were observed between the LCN2-silenced and control cells. Microarray analysis indicated that LCN2 acted by influencing genes involved in protein metabolism, stress response, cell cycle and proliferation. Conclusions: Our results suggest that LCN2 upregulation protects hepatocytes from IL-1β-induced stress. Additionally, our microarray analysis of LCN2-silenced and control cells provides a better understanding of the mechanisms that may be influenced by LCN2 induction.